Penerapan Data Mining Penjualan Alat Tulis Kantor Menggunakan Algoritma Apriori Di Tiga Balata - Muhammad Aliyul Amri; Syafitri Warda Ningsih (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Data mining is a process of searching for patterns or interesting information in selected data using certain techniques or methods. Data mining is a process of searching for patterns or interesting information in selected data using certain techniques or methods. This research discusses the Association Rule method as a data mining function which is implemented using the Apriori Algorithm. The priori algorithm is the most well-known algorithm for finding high frequency patterns. For this reason, this algorithm can combine items or items sold in stationery stores. The combination values obtained were two item combinations, namely Notebooks, Pens and Double Folio Paper, and Pens with a Support value of 13.64% each. By doing this research, the shop owner will be able to provide items that are often purchased by consumers and can be a consideration for the layout of the items in the stationery shop.